2017
DOI: 10.1186/s12879-017-2319-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus, Epstein-Barr virus and varicella zoster virus infection in the first two years of life: a cohort study in Bradford, UK

Abstract: BackgroundCytomegalovirus (CMV), Epstein Barr virus (EBV) and varicella-zoster virus (VZV) are common herpesviruses frequently acquired in childhood, which establish persistent, latent infection and are likely to impact the developing immune system. Little is known about the epidemiology of CMV and EBV infections in contemporary UK paediatric populations, particularly whether age at infection differs by ethnic group.MethodsChildren enrolled in the Born in Bradford Allergy and Infection Study had a blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
(55 reference statements)
1
26
0
Order By: Relevance
“…EBV infection tends to be acquired later than CMV; in this cohort, most of the CMV infections occurred in the first year, usually through contact with the mother, whereas most EBV infections occurred in the second year via contact with siblings and other children. 26 The 18% prevalence of atopy in our study is generally consistent with results from other European birth cohorts 19,46 and UK studies. 47,48 Some of these measured allergen-specific IgE (sIgE) in serum rather than SPT, and the children included ranged from age 2 to 7 years with all primary school-aged children included in one study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…EBV infection tends to be acquired later than CMV; in this cohort, most of the CMV infections occurred in the first year, usually through contact with the mother, whereas most EBV infections occurred in the second year via contact with siblings and other children. 26 The 18% prevalence of atopy in our study is generally consistent with results from other European birth cohorts 19,46 and UK studies. 47,48 Some of these measured allergen-specific IgE (sIgE) in serum rather than SPT, and the children included ranged from age 2 to 7 years with all primary school-aged children included in one study.…”
Section: Discussionsupporting
confidence: 92%
“…The findings for age at CMV infection were compared between the univariable and multiple logistic regression analyses, and no evidence of multicollinearity was found, so the multiple regression analysis was accepted as the final model. Birth order and duration of breastfeeding were included in the CMV model a priori as these are strongly associated with age at CMV infection and associated with atopy in other studies . Effect modification by sex and ethnic group was investigated …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the neonatal period, the incidence of CMV infection varies according to race, economic status, and environmental factors. One study showed that one-third of Pakistani children had CMV infection by the age of 12 months, compared to only 9% of white British children [ 25 ]. In another study, most preschool children (>90%) in South America, East Asia, and India were CMV seropositive, in contrast, seroepidemiologic surveys in Great Britain and in USA have found that less than 20% of children of similar age were seropositive [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mode of transmission varies from direct contact to nosocomial and transplacental transmission from mother to fetus, resulting in congenital cytomegalovirus with an estimated incidence in developed countries that ranges from 0.6% to 0.7% of all live births. The risk factors for transmission include low socioeconomic status, sexual activity, overcrowding, and increasing birth order [ 47 - 49 ].…”
Section: Reviewmentioning
confidence: 99%